Recyclable synthesis of mesityl iodonium(III) salts. Issue 26 (28th June 2019) - Dohi, Toshifumi; Hayashi, Takumi; Ueda, Shohei; Shoji, Toshitaka; Komiyama, Keina; Takeuchi, Hitoshi; Kita, Yasuyuki
Abstract: An efficient protocol for C–H condensation of hypervalent iodine compounds toward arenes in fluoroalcohols has been applied to the recyclable preparation of mesityl iodonium(III) salts. The electrophilicities of [hydroxy(tosyloxy)iodo]mesitylene (MesI(OH)OTs) and iodomesitylene diacetate (MesI(OAc)2 ) are suitably enhanced in 2, 2, 2-trifluoroethanol. A series of nucleophilic aromatic compounds react smoothly with MesI(OH)OTs and MesI(OAc)2 or in situ hypervalent iodine(III) species, generated from iodomesitylene, to provide the target mesityl iodonium(III) salts in good yields at room temperature with broad functional group tolerance. This C–H condensation strategy merits high para -regioselectivities during the diaryliodonium(III) salt formation, but the major limitation in the case of low-reactive aromatic substrates is byproduct formation resulting from the self-condensation of the nucleophilic mesitylene ring in MesI(OH)OTs and MesI(OAc)2 . Graphical abstract: Image 1